PET/CT-derived coronary calcium score may predict cardiac complications in anthracycline-treated patients with lymphoma - Genevieve Douglas; Zoe Loh; Evonne S.Y. Shum; Sze-Ting Lee; Niamh Waters; Garry Hamilton; Geoffrey Chong; Alexandra C. Murphy; Eliza A. Hawkes (Blood Advances)
Abstract: Anthracycline-mediated cardiotoxicity is a common concern after lymphoma therapy, particularly in patients with high cardiovascular risk (CVR). In noncancer populations, coronary artery calcium scoring (CACS) effectively identifies individuals who may benefit from aggressive CVR modification to lower the risk of cardiovascular events. Emerging evidence suggests that CACS can also predict cancer therapy-related cardiotoxicity, potentially identifying candidates for cardioprotective strategies. Our study aimed to evaluate whether CACS obtained from pretreatment positron emission tomography (PET)/computed tomography (CT) scans could stratify cardiac event risk in patients with lymphoma receiving anthracycline-based chemotherapy. We enrolled 358 consecutive patients with lymphoma treated between 2012 and 2022, calculating the CACS from their pretreatment PET/CT. We reviewed medical records to identify pre-existing cardiac conditions, CVR, and posttreatment cardiac events, including coronary events, heart failure (HF), and arrhythmias. Logistic and Cox regression models were used to assess associations between CVR, CACS categories (CACS = 0, CACS 1-400, CACS >400), and new cardiac events. At a median follow-up of 27 months (95% confidence interval [CI], 22.3-31.7) in patients without cardiac history, 10% experienced posttreatment cardiac events (HF, 14; arrhythmias, 9; coronary event, 1; combination, 8). Patients with a CACS >0 had more events (21 total, 20% vs 11 total, 5.4% for CACS = 0; P < .001). Elevated CACS was independently associated with HF (CACS 1-400: odds ratio [OR], 3.73; 95% CI, 1.21-11.43; P = .022; CACS >400: OR, 5.43; 95% CI, 1.47-20.03; P = .011) and any cardiac event (CACS 1-400: OR, 2.48; 95% CI, 1.02-6.04; P = .045; CACS >400: OR, 3.28; 95% CI, 0.91-10.68; P = .029). CACS may effectively stratify patients with lymphoma at risk of cardiac complications, thereby identifying a group poised to benefit from targeted preventive strategies.